Porcine Liver Normothermic Machine Perfusion: Methodological Framework and Potential Pitfalls - Nicholas Gilbo, PhD; Tine Wylin, PhD; Veerle Heedfeld, MSc; Ina Jochmans, PhD; Jacques Pirenne, PhD; Peter Friend, PhD; Diethard Monbaliu, PhD (Transplantation Direct, 2022)
Porcine models of liver normothermic machine perfusion (NMP) are increasingly used in transplant research, although known to be challenging because of their complex methodology and their scarcely documented operational aspects. Here, we aimed to provide a methodological framework for researchers looking to adopt NMP technology in research setting by giving an in-detail account of the implementation of a previously validated porcine liver NMP model. We subjected groups of 3–5 porcine livers to 24 h NMP and, using a trial-and-error principle, introduced stepwise changes in the NMP setting with the objective to obtain stable preservation of liver function and histology for 24 h. Female porcine livers were procured, and packed red-blood-cell perfusate was prepared. Perfusate oxygenation, hemodynamics, markers of hepatic injury (aspartate transaminase [AST]), function (lactate, perfusate pH, bile production), and histology were analyzed. Intermediate analysis was performed within groups and a minimum of 3 (out of 5) failed experiments prompted methodological reevaluation. Overall, 13 liver NMP experiments were needed in 3 phases. In phase 1, loss of oxygenator performance occurred from 6 h onward in 3 consecutive experiments because of perfusate leakage. In phase 2, a plasma-tight hollow fiber oxygenator ensured adequate perfusate oxygenation in 5 experiments. However, portal vein resistance increased during all liver NMP, associated with high perfusate AST levels (range, 106–322 IU/L/100 g) and pan-lobular sinusoidal dilation and hemorrhage, suggesting liver outflow impairment. In phase 3, an improved inferior vena cava cannulation technique avoided liver outflow impairment, resulting in lower AST release (range, 29–101 IU/L/100 g), improved lactate clearance, preserved biliary excretion, and normal histology in 5 experiments. This study underscores the critical importance of auditing all equipment and operational components of NMP circuits to obtain successful and reproducible perfusion setup and advocates for in-detail reporting of methodological aspects and potential pitfalls.